Desempenho de plantas de Jatropha curcas L. cultivadas em duas localidades do Estado do Espírito Santo - Pereira, Pedro Mazzocco (2014)
This study aimed at assessing the developement of Jatropha curcas plants (Jatropha curcas L.) grown at two locations in Espírito Santo: Itarana and Pontal do Ipiranga. In order to do that, measurements were performed between December 2012 and April 2013 regarding the vegetative and reproductive phenology, gas exchange, transient and modulated chlorophyll a fluorescence and chlorophyll index. During the assessment period it occurred the hightest blooming season of plants grown in Itarana, between the months of December and January, and the largest number of nuts was found in March. Plants grown in Pontal do Ipiranga showed lower growth of shoots and low production of inflorescences, flowers and fruits. There was a drop of older leaves during the period of greatest water stress and regrowth after the first rains in the region of Pontal do Ipiranga while in the region of Itarana there was no leaf drop during the analysis period. Gas exchange showed the highest rates in Itarana at the beginning of the reproductive period and gradual fall over the months, while in the region of Pontal do Ipiranga the reverse occurred and the highest rates of net photosynthesis took place at the end of the fruiting period. The analysis of the kinetic difference (?VOP) indicates positive differences in the leaves of plants grown in Pontal do Ipiranga, which clearly demonstrate the inhibition of electron transport between PSII and PSI in the first three months (December, January and February). It was observed the appearance of a K-band, an indicative of damage in the process of photooxidation of water in the water-splitting complex, decreased connectivity of the units that form the PSII reaction center - evidenced by the appearance of positive L-Band and a positive G-band indicative of damage in the plastoquinone-pool level and impaired efficiency of PSI in the plants of Pontal do Ipiranga - in the months of January, February and March. Whereas the development of culture is affected by the levels of photosynthetically active radiation, seasonality of temperature and rainfall make it necessary to consider the physiological variables during the modeling of agroclimatic zoning. It is inferred, therefore, that the plants which possessed better crop performance were the plants grown in the town of Itarana